1989
DOI: 10.1128/aac.33.11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Teicoplanin pharmacokinetics in patients undergoing continuous ambulatory peritoneal dialysis after intravenous and intraperitoneal dosing

Abstract: The pharmacokinetics of teicoplanin after single 6-mg/kg intravenous and intraperitoneal doses were studied in five noninfected patients undergoing continuous ambulatory peritoneal dialysis. Biological samples were assayed for teicoplanin content (9,23,28). Numerous studies in humans have documented its efficacy in the treatment of septicemia, endocarditis, and skin and skin structure infections caused by these organisms (2,5,11,15,16,29,31,32).Preliminary human pharmacokinetic data suggest that teicoplanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
1
3
1
Order By: Relevance
“…drug exposure (Table 3). These results are in good agreement with data for other antibiotics, such as fosfomycin, cefotaxime, teicoplanin, vancomycin, and aminoglycosides (3,12,13).…”
Section: Discussionsupporting
confidence: 81%
“…drug exposure (Table 3). These results are in good agreement with data for other antibiotics, such as fosfomycin, cefotaxime, teicoplanin, vancomycin, and aminoglycosides (3,12,13).…”
Section: Discussionsupporting
confidence: 81%
“…However, concentrations of teicoplanin in the dialysate 48hours after its administration remained significantly below the therapeutic range [Figure1(b)]. In other studies, teicoplanin was administered intravenously at doses of 3and 6mg/kg in patients on C APD (12)(13)(14). In those studies, the achieved serum levels were significantly lower than those of the present study, whereas detected concentrations of teicoplanin in the dialysate were below 1 µg/mL.…”
Section: Discussioncontrasting
confidence: 57%
“…Teicoplanin has been administered both intravenously and intraperitoneally in anuric patients undergoing CAPD, but at dose regimens not achieving serum concentrations within the therapeutic range (11)(12)(13)(14). The present study was designed to evaluate the pharmacokinetics of teicoplanin after a single intravenous dose higher than those already applied in patients on CAPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 29 Previous studies were mostly confined to adult population with various settings of renal replacement therapy since the early era of teicoplanin. 30 31 32 33 34 In those studies, adult patients with renal failure tended to have prolonged half-life and reduced total body clearance of teicoplanin, while volume of distribution varied. Lam et al 35 have suggested a nomogram for dosage adjustment in adults with varying degrees of renal failure.…”
Section: Discussionmentioning
confidence: 99%